2008
DOI: 10.1289/ehp.11371
|View full text |Cite
|
Sign up to set email alerts
|

S -Ethyl- N,N -dipropylthiocarbamate Exposure and Cancer Incidence among Male Pesticide Applicators in the Agricultural Health Study: A Prospective Cohort

Abstract: BackgroundThe Agricultural Health Study (AHS) is a prospective cohort study of licensed pesticide applicators from Iowa and North Carolina enrolled between 1993 and 1997. EPTC (S-ethyl-N,N-dipropylthiocarbamate) is a thiocarbamate herbicide used in every region of the United States. The U.S. Environmental Protection Agency reports that EPTC is most likely not a human carcinogen; however, the previous epidemiologic data on EPTC exposure and cancer risk were limited.ObjectivesThe purpose of this study was to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
1
44
0
1
Order By: Relevance
“…The results of the present study showed increased risk of gastrointestinal cancers in people who were at the highest level of exposure to pesticides. These findings were consistent with the results of some studies on the effects of different levels of exposure to pesticides on gastrointestinal cancers (16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study showed increased risk of gastrointestinal cancers in people who were at the highest level of exposure to pesticides. These findings were consistent with the results of some studies on the effects of different levels of exposure to pesticides on gastrointestinal cancers (16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 92%
“…Overall cancer incidence was increased among applicators in the highest exposure categories for diazinon (Beane Freeman et al 2005) and S-ethyl-N,N-dipropylthiocarbamate (EPTC) (van Bemmel et al 2008) relative to nonexposed applicators, and significant exposure-response trends were observed for both pesticides with both exposure measures. None of the other pesticides Alavanja et al (2003Alavanja et al ( , 2004, Andreotti et al (2009), and Lee et al (2007b); all others are RRs.…”
Section: Study Summariesmentioning
confidence: 99%
“…65 although the risk associated with both of these herbicides was limited to the highest exposure group and thus further follow-up will be necessary.…”
mentioning
confidence: 99%
“…Recent epidemiological evidence linking specific pesticides to leukemia has established hypotheses that need to be evaluated in other studies (eg, the associations between leukemia overall and diazinon [an OP insecticide currently in widespread use] and several OC insecticides no longer in use in the United States or other developed countries are of particular interest). 65,66,[146][147][148][149][150][151] Linking leukemia to specific pesticides that are used at high levels occupationally should help to identify the chemical agents responsible for childhood cancers as well. The use of preclinical biomarkers (eg, monoclonal B-cell lymphocytosis) to study the etiology of CLL may be a powerful approach for this leukemia subtype.…”
mentioning
confidence: 99%